Wavelet-based frame video coding algorithms using fovea and SPECK. (March 2018) - Galan-Hernandez, J.C.; Alarcon-Aquino, V.; Starostenko, O.; Ramirez-Cortes, J.M.; Gomez-Gil, Pilar
Abstract: Current video coding standards such as the H.264 or Advanced Video Coding (AVC) and the H.265 or High Efficiency Video Coding (HEVC) are based on the Integer Discrete Cosine Transform (IDCT). However, it has been shown that wavelet-based algorithms have better performance than IDCT-based algorithms for still images. Also, exploiting the human visual system characteristics in stationary point of view image and video transmissions like the fovea aliasing can improve the quality of the reconstructed image. In this paper, two wavelet-based video coding approaches called SPECK-based Codec (SP-Codec) and Adaptive Wavelet/Fovea-based Codec (AWFV-Codec) are proposed. The proposed SP-Codec approach applies the Set Partitioned Embedded Block Codec (SPECK) wavelet-based compression algorithm in order to increase the intra-frame coding quality. The second proposed approach AWFV-Codec uses the Adaptive Fovea Set Partitioned Embedded Block Codec (AFV-SPECK) fovea wavelet-based compression algorithm for intra-frame coding. Fovea based compression allows to increase the quality of the reconstructed frames over regions of interest (ROI). A comparison of the proposed algorithms against the HEVC based on IDCT approach shows how the proposed wavelet-based schemes achieve higher compression ratios and higher reconstruction quality. When fixation point of view is stationary, the proposed wavelet/fovea-based algorithm achieves better quality at lower compression ratios than the wavelet-based only proposed algorithm.